Brain Tumor Detection from MRI Image Using Deep Learning - Ghosh, Debjyoti; Roy, Utpal (International Journal of Computer Sciences and Engineering, 2025)
Nowadays it is believed that Brain tumor is one of the most harmful diseases that may lead to serious cancer. Major issue of the treatment of brain tumor is early detection of it before leading to malignant stage. More importantly early diagnosis of brain tumors plays an important role in improving further treatment possibilities and thus increases the survival rate of the patients. Here in this study, we have developed a system that can accurately detect tumor from brain Magnetic Resonance Imaging (MRI) images. To do this we have prepared a laboratory made moderate size database collecting various types of brain Magnetic Resonance Imaging images. In this experiment the brain MRI image has been preprocessed first, then the image has been separated into tumor or non-tumor portion of the image using deep neural net.